2021
DOI: 10.32710/tekstilvekonfeksiyon.767428
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Recycled Polyester (rPET) Filament Fiber Properties on Various Woven Fabric Performance Properties

Abstract: In order to reduce the requirement of waste eliminating and environmental pollution, recycling seems to be a suitable solution. In this study, polyester fibers with three different number of filament and two fiber cross section form (round and plus) were spun from recycled polyethylene terephthalate (rPET) polymer and texturised on an industrial scale. rPET yarns were used as a weft yarn in woven fabric production. Fabric performance properties such as breaking, tearing and seam slippage resistance, weight, br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…The abrasion resistance of textile materials is an important feature that determines the lifespan of fabrics. 16 The abrasion resistance of the fabric samples was evaluated by the mass loss difference between the masses before and after abrasion cycles. It is observed that all swimwear fabric samples withstand 15,000 rubbing cycles without any damage.…”
Section: Seam Strength and Abrasion Resistancementioning
confidence: 99%
See 2 more Smart Citations
“…The abrasion resistance of textile materials is an important feature that determines the lifespan of fabrics. 16 The abrasion resistance of the fabric samples was evaluated by the mass loss difference between the masses before and after abrasion cycles. It is observed that all swimwear fabric samples withstand 15,000 rubbing cycles without any damage.…”
Section: Seam Strength and Abrasion Resistancementioning
confidence: 99%
“…In order to achieve the required material properties and performance, recycled fibers can be blended with virgin fibers. 5,6,[14][15][16] Nowadays, some brands, such as Econyl, Repreve, Amni Soul Eco®, Batoko have focused on promoting the use of recycled synthetic fibers in swimwear design to reduce the environmental impact of synthetics. 16,17 In this study, the effect of recycled fiber content on the performance/quality properties of swimwear fabrics was investigated, with the aim of contributing to the circular economy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation